Lectotypification of four Lacaita’s names in the genus Centaurea (Asteraceae) - Wagensommer, Robert P.; Perrino, Enrico V.; Albano, Antonella; Medagli, Pietro; Passalacqua, Nicodemo G. (Phytotaxa, 2016)
The following four plant names published by Charles (Carlo) Carmichael Lacaita are lectotypified: Centaurea diomedea var. iapygica, Centaurea diomedea f. ambigua, Centaurea leucadea and Centaurea leucadea f. ambigua (Asteraceae).